Literature Review of Concurrent Engineering in Kansei Engineering and Ergonomic - Setiawan, Alvin; Ginting, Rosnani; Ishak, Aulia (TALENTA Publisher, 2024)
This research aims to conduct a literature review on the application of the integration of Kansei engineering, ergonomics, and concurrent engineering methods in the context of product design. A systematic study of 8 scholarly journals related to the topic in the last decade indicates that combining these three methods has a positive impact on product performance and the efficiency of the development process. In conclusion, a multidisciplinary approach is highly recommended to produce innovative and highly competitive products through a faster and cost-effective process.